2007
DOI: 10.1051/0004-6361:20067032
|View full text |Cite
|
Sign up to set email alerts
|

A 0535+26 in the August/September 2005 outburst observed by RXTE and INTEGRAL

Abstract: Aims. In this Letter we present results from INTEGRAL and RXTE observations of the spectral and timing behavior of the High Mass X-ray Binary A 0535+26 during its August/September 2005 normal (type I) outburst with an average flux F (5−100) keV ∼ 400 mCrab. The search for cyclotron resonance scattering features (fundamental and harmonic) is one major focus of the paper. Methods. Our analysis is based on data from INTEGRAL and RXTE Target of Opportunity Observations performed during the outburst. The pulse peri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
110
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 24 publications
19
110
3
Order By: Relevance
“…A similar overall shape has been found in a wide range of observations over several decades in time and outbursts of quite different peak brightness (e.g., Bradt et al 1976 and more recently Kretschmar et al 2005, Finger et al 2006, Camero-Arranz 2007, and Caballero et al 2007.…”
Section: Pulse Profile Overviewsupporting
confidence: 77%
See 3 more Smart Citations
“…A similar overall shape has been found in a wide range of observations over several decades in time and outbursts of quite different peak brightness (e.g., Bradt et al 1976 and more recently Kretschmar et al 2005, Finger et al 2006, Camero-Arranz 2007, and Caballero et al 2007.…”
Section: Pulse Profile Overviewsupporting
confidence: 77%
“…A possible explanation was bursts of wind-like accretion from capture of low angular momentum material, while the higher angular momentum material forms an accretion disk, which feed the main part of the outburst. Caballero et al (2007Caballero et al ( , 2008 found a change of the cyclotron line energy up to ∼50 keV during this period and no significant change in the spin frequency up to the time the main outburst began. Postnov et al (2008) proposed that magnetospheric instabilities developing at the onset of the accretion were the origin of the flaring activity.…”
Section: Pulse Profile Studymentioning
confidence: 84%
See 2 more Smart Citations
“…The source reappeared in a Type II outburst in May/June 2005 and was detected by Swift (Tueller et al 2005) and RHESSI (Smith et al 2005). It was subsequently seen to undergo a Type I outburst in August 2005 (Kretschmar et al 2006;Caballero et al 2007).…”
Section: Systems Containing a Giant Donormentioning
confidence: 99%